Characteristics of High School Physics Problem-Solving Skills and Integrating the PBL Model Assisted by E-Book - Irgy Redityo Dawana; Dwikoranto Dwikoranto (IKIP Mataram, 2024)
This research discusses the implementation of the Problem-Based Learning model assisted by E-Book to improve students' problem-solving skills on renewable energy materials. The purpose of this research is to identify the characteristics of physics problem-solving through the knowledge profile of students at the high school level as a consideration in the application of the PBL model and the use of E-Book assisted learning media to improve problem-solving skills. The research method used is a preliminary study with qualitative descriptive analysis. The instruments used include the problem-solving skills test, interview questionnaire, and student response questionnaire. The data analysis technique in this study used a problem-solving skills test questionnaire and a survey to get responses from students. The findings showed that students' problem-solving skills were generally in the low category. Of the total learners, 87 students were in the low category, 2 students in the medium category, and 1 student in the high category. Although students have been able to understand the problem, they still experience problems in providing answers and checking back due to lack of habit in working on problem-solving-based problems. Therefore, it is necessary to practice and use learning models, as well as E-Book technology, which can help in the process of teaching and learning activities and increase students' learning motivation. Thus, it is expected that students' problem-solving skills can be improved through the right learning approach and the use of relevant technology.